“ANALISIS PENGARUH PROGRAM PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI DI RUMAH SAKIT UMUM DAERAH ARIFIN AHMAD PROPINSI RIAU” - Lastriani, Elvi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2015)
Activity of Education and training is very important thing for Service Companywhere Arifin Achmad Public Hospital Area of Riau Province represents theorganization which is active in governmental property health service. At theemulation condition which progressive vastly in environment of business thatavailable of health service, management of Arifin Achmad Public Hospital Areaof Riau Province striving that human resource performance could increase thequality by following education and training which is provided. Development effortconducted for all good employees include medical employment, paramedic oftreatment employment, paramedic of non treatment employment and non medicalemployment. At the end, the training and education program expected to able toincrease the skill, knowledge and employees ability so that can improve theemployee’s performance.The reasons of the research are to know that: 1. The factor of education andtraining by performance together of employees of Arifin Achmad Public HospitalArea of Riau Province, 2. How far the education and training program partiallyhave an effect to the performance of employees of Arifin Achmad Public HospitalArea of Riau Province, 3. which factor dominantly having an effect toperformance of employees of Arifin Achmad Public Hospital Area of RiauProvince. This research is conducted to 90 employees from 888 employees.Analyzer used by analysis factor and regression analyze. The result from thisresearch is found 4 factors that influencing performance of employees of ArifinAchmad Public Hospital Area of Riau Province base on the percentage of eachvariant, are 1. Factor of items of education and training (84,320), 2. Factor ofmethod of short education (66,195), 3. Factor of management of short education(68,66), 4. Factor of applying of items of short education (66,305%). While mostfactor that having an effect to employees performance is factor of applying ofitems of education and training with the value of beta equal to 0,467 andcoefficient of partial determination equal to 43,43%.